On operations operational art and military disciplines - Friedman, B. A. (Brett A.) (Naval Institute Press, 2021)
"On Operations: Operational Art and Military Disciplines traces the history of the development of military staffs and ideas on the operational level of war and operational art from the Napoleonic Wars to today, viewing them through the lens of Prussia/Germany, the Soviet Union, and the United States"--